PERANCANGAN KOMIK SEJARAH JEMBATAN RATAPAN IBU DI PAYAKUMBUH - Febri Ferdian, Drs. Abd. Hafiz, M.Pd, Drs. Mediagus (Serupa The Journal of Art Education, 2016)
This report aims to visualisating the story that has ever happened In the Ratapan Ibu Bridge into the medium of comics with cartoon style. The method that use is made comic with kartunal style. The stage is : 1) Preparation, finding the idea of art in reference about the Ratapan Ibu Bridge. 2) Elaboration, analyzing and summarizing the datas from the field, the history books, and articles from the internet. 3) Synthesis, decided techniques used for the process of creating the work. 4) The realization of the concept, a scenario stories and create. 5) The completion, re-evaluation the work. The result of the creation tell that Wira is a student of the high school being dragged to the days of 1949 and saw the tragedy that occurred on the Ratapan Ibu Bridge, in the end of story Wira back to the days of 2015.Kata kunci: Perancangan, Komik, Sejarah Jembatan Ratapan Ibu di Payakumbuh